2016
DOI: 10.1515/fhort-2016-0002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intercropping carrot (Daucus carota L.) with two aromatic plants, coriander (Coriandrum sativum L.) and summer savory (Satureja hortensis L.), on the population density of select carrot pests

Abstract: Intercropping, or the use of different aspects of the interaction between organisms in ecosystems, can be classified as an ecological method that limits harmful human interference in the environment, especially the consumption of chemicals. The impact of intercropping carrot with coriander Coriandrum sativum L. and summer savory Satureja hortensis L. on the occurrence of select carrot pests was estimated in the years 2010-2011. Intercropping had a significant effect on the decrease of the number of roots damag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…Another study showed that intercropping carrot with coriander increased syrphid abundance compared with carrot alone. 48 Ladybeetle abundance was also higher in bean plots intercropped with coriander. Previous studies showed that coriander plants intercropped with carrot, 48 tomato, 34 cabbage, 33 and eggplant 49 had higher abundance and diversity of coccinellids species than their respective monocrops, likely as a result of the attractiveness, and suitability as food, of coriander flowers for adult ladybeetles.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…Another study showed that intercropping carrot with coriander increased syrphid abundance compared with carrot alone. 48 Ladybeetle abundance was also higher in bean plots intercropped with coriander. Previous studies showed that coriander plants intercropped with carrot, 48 tomato, 34 cabbage, 33 and eggplant 49 had higher abundance and diversity of coccinellids species than their respective monocrops, likely as a result of the attractiveness, and suitability as food, of coriander flowers for adult ladybeetles.…”
Section: Discussionmentioning
confidence: 88%
“…Morris and Li also found that coriander used as a companion plant together with cabbage attracted large numbers of syrphid flies. Another study showed that intercropping carrot with coriander increased syrphid abundance compared with carrot alone . Ladybeetle abundance was also higher in bean plots intercropped with coriander.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As in intercropping systems, two or more crops can be planted in the same area (Tung et al 2016), maintaining the biodiversity of floral and feeding resources for natural enemies, thus contributing to the reduction of pest population in cotton (Fernandes et al 2012;Rao et al 2012), causing impact on insect dynamics in intercropping systems (Altieri & Letourneau 1982). Several studies have shown that agroecosystem diversification can reduce pest infestation (Jankowska & Wojciechowicz-Żytko 2016). The understanding of diversity plant effect on herbivorous control is relevant for the understanding of agricultural sustainability (Dassou & Tixier 2016).…”
Section: Introductionmentioning
confidence: 99%